2012
DOI: 10.1111/myc.12029
|View full text |Cite
|
Sign up to set email alerts
|

Histoplasmosis: a new endemic fungal infection in China? Review and analysis of cases

Abstract: Histoplasmosis occurs in specific endemic areas, including the mid-western United States, Africa and most of Latin America. Sporadic cases have also been reported in China. The aim of this study was to summarise the epidemiological and clinical data of histoplasmosis in China. We searched the PubMed, CBMdisk and CNKI databases to identify publications related to histoplasmosis in China. Case reports/series on patients with histoplasmosis were included. A comprehensive literature review identified additional ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
79
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 35 publications
6
79
1
3
Order By: Relevance
“…13 Skin lesions are also more common with South American histoplasmosis, 14 possibly because of underlying genetic differences in fungal strains. In contrast, cutaneous lesions are infrequent in cases of histoplasmosis in Asia (6.6% in a study form China), 3 but notably, both the patient described here and the previously reported case from the Philippines presented with disseminated papular lesions, some of which were umbilicated lesions. Skin lesions in histoplasmosis can be easily confused with those of penicilliosis, an endemic fungal infection in southeast Asia, as well as cryptococcal skin lesions, common in patients with AIDS.…”
Section: Discussionmentioning
confidence: 53%
“…13 Skin lesions are also more common with South American histoplasmosis, 14 possibly because of underlying genetic differences in fungal strains. In contrast, cutaneous lesions are infrequent in cases of histoplasmosis in Asia (6.6% in a study form China), 3 but notably, both the patient described here and the previously reported case from the Philippines presented with disseminated papular lesions, some of which were umbilicated lesions. Skin lesions in histoplasmosis can be easily confused with those of penicilliosis, an endemic fungal infection in southeast Asia, as well as cryptococcal skin lesions, common in patients with AIDS.…”
Section: Discussionmentioning
confidence: 53%
“…Most of the patients were from regions through which the Yangtze River flows. 4 These regions include the two provinces where our patient had resided. Our patient had never been abroad.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, sporadic cases of autochthonous histoplasmosis have been encountered in China, which was traditionally considered nonendemic for H. capsulatum. [2][3][4] Recently, a multilocus sequence typing (MLST) approach and a sequence database were available for H. capsulatum, which helped us to better understand the molecular epidemiology of this disease. 5 Here, we reported a case of disseminated histoplasmosis in an human immunodeficiency virus (HIV)-negative patient who had never been outside China.…”
Section: Introductionmentioning
confidence: 99%
“…Histoplasmosis usually presents as in immune-compromised individuals with serious underlying disease, including AIDS [10,11]. The occurrence of histoplasmosis in Asia has been recently reviewed with cases of histoplasmosis from India, Malaysia, Singapore, Indonesia, Thailand, South Vietnam and Japan, but the autochthonous nature of the cases reported has not been established unequivocally [8,12,13]. Recently, H. capsulatum was recovered from environmental sources contaminated with bat guano and chicken droppings in Thailand [14].…”
Section: Introductionmentioning
confidence: 99%
“…Most Histoplasma infections are subclinical, however, occasionally disease occurs linked in to the host immune response [4]. The disease is the most common pulmonary mycosis in North America and Central America, but the organism is known to exist in many areas around the world [5][6][7][8][9]. Histoplasmosis usually presents as in immune-compromised individuals with serious underlying disease, including AIDS [10,11].…”
Section: Introductionmentioning
confidence: 99%